Proportion of clinical holistic responders in patients with persistent spinal pain syndrome type II treated by subthreshold spinal cord stimulation compared to best medical treatment: a study protocol for a multicentric randomised controlled trial (TRADITION) - Lisa Goudman; Koen Putman; Leen Van Doorslaer; Maxime Billot; Manuel Roulaud; Philippe Rigoard; TRADITION consortium; Maarten Moens (Trials, 2023)
Abstract Background Integrating information on bodily functions, pain intensity and quality of life into one composite measure of a holistic responder has recently been proposed as a useful method to evaluate treatment efficacy of spinal cord stimulation (SCS) in patients with therapy-refractory persistent spinal pain syndrome type II (PSPS-T2). Previous studies already demonstrated the efficacy of standard SCS over best medical treatment (BMT) and the superiority of new subthreshold (i.e. paresthesia free) SCS paradigms compared to standard SCS. Nevertheless, the efficacy of subthreshold SCS compared to BMT has not yet been investigated in patients with PSPS-T2, neither with unidimensional outcomes nor with a composite measure. The current objective is to examine whether subthreshold SCS, compared to BMT, provided to patients with PSPS-T2 results in a different proportion of clinical holistic responders (as composite measure) at 6 months. Methods A two-arm multicentre randomised controlled trial will be conducted whereby 114 patients will be randomised (1:1) to (a) BMT or (b) paresthesia-free SCS. After a follow-up period of 6 months (primary time endpoint), patients receive the opportunity to cross over towards the other treatment group. The primary outcome is the proportion of clinical holistic responders at 6 months (i.e. a composite measure of pain intensity, medication, disability, health-related quality of life and patient satisfaction). The secondary outcomes are work status, self-management, anxiety, depression and healthcare expenditure. Discussion Within the TRADITION project, we propose to shift the focus from a unidimensional outcome measure towards a composite measure as primary outcome measure to evaluate the efficacy of currently used subthreshold SCS paradigms. The lack of methodologically rigorous trials exploring the clinical efficacy and socio-economic consequences of subthreshold SCS paradigms is pressing, especially in light of the growing burden of PSPS-T2 on the society. Trial registration ClinicalTrials.gov NCT05169047. Registered on December 23, 2021